2007
DOI: 10.1161/strokeaha.107.491126
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Hypertensive Rats Are Highly Vulnerable to AMPA-Induced Brain Lesions

Abstract: Background and Purpose-Whereas the effects of chronic arterial hypertension on the cerebral vasculature have been widely studied, its effects on brain tissue have been studied less so. Here we examined if spontaneously hypertensive rats (SHRs) or the normotensive control Wistar Kyoto rats (WKYs) made hypertensive by renal artery stenosis (R-WKYs) are vulnerable to an excitotoxic brain lesion provoked by an overactivation of glutamate receptors. Methods-Lesion volumes were quantified by histology in WKYs and SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Nonetheless, data exist in the literature, although to a lesser extent, relative to SHR-SP, to show that hypertension per se does not entirely underlie the sensitivity of SHR to cerebral ischemia (Lecrux et al, 2007). Indeed, we have previously shown that 7-week-old SHR, in which hypertension is not yet established, also exhibit exacerbated ischemic brain damage when compared with agematched WKY (Lecrux et al, 2007). On the basis of these observations, we have used another wellcharacterized model of nongenetic hypertension, induced by renal artery stenosis in WKY (Del Bigio et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nonetheless, data exist in the literature, although to a lesser extent, relative to SHR-SP, to show that hypertension per se does not entirely underlie the sensitivity of SHR to cerebral ischemia (Lecrux et al, 2007). Indeed, we have previously shown that 7-week-old SHR, in which hypertension is not yet established, also exhibit exacerbated ischemic brain damage when compared with agematched WKY (Lecrux et al, 2007). On the basis of these observations, we have used another wellcharacterized model of nongenetic hypertension, induced by renal artery stenosis in WKY (Del Bigio et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, eutrophic and hypertrophic remodeling of the brain arteries and the shift of the autoregulation curve are well-known hallmarks of the vascular changes induced in SHR (Mulvany et al, 1978). Nonetheless, data exist in the literature, although to a lesser extent, relative to SHR-SP, to show that hypertension per se does not entirely underlie the sensitivity of SHR to cerebral ischemia (Lecrux et al, 2007). Indeed, we have previously shown that 7-week-old SHR, in which hypertension is not yet established, also exhibit exacerbated ischemic brain damage when compared with agematched WKY (Lecrux et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, overactivation of N-methyl-D-aspartic acid (NMDA) receptors leads to an increase in intracellular calcium levels and/or detrimental signaling pathways, which in turn can directly or indirectly cause much of the downstream damaging processes associated with ischemic stroke. In contrast, the SH rat has been shown to be much more sensitive than other strains to a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor activation (which has different downstream effects to NMDA) and to be relatively resistant to NMDA activation (Lecrux et al, 2007). To this end, JNKI-1D-TAT has shown high efficacy after NMDA excitotoxicity (Borsello et al, 2003) and we have also shown efficacy of PYC36D-TAT (and JNKI-1D-TAT) after NDMA exposure (unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of these models are that they are easy to manipulate, relatively cost-effective, and cell death can be readily measured and quantitated. However, signaling pathways can be altered by the culturing conditions used 3,4 , and immature neurons and immortalized lines can express different receptors and signaling molecules when compared to mature brain [5][6][7][8] . Furthermore, cultured neurons only allow the examination of one cell type (or two, if a coculture system is used), whereas intact brain tissue is heterogeneous, containing a variety of cell types that interact with each other.…”
Section: Introductionmentioning
confidence: 99%